Rancang Bangun Sistem Informasi Pemasaran pada CV Anugrah Sejati Prima Berbasis Website Menggunakan Framework Scrum - Dwi Haryani; Firmansyah Ibrahim; Zulkarnaim Mahsyur (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2022)
CV Anugerah Sejati Prima is a business entity engaged in the sale of goods/tools, selling various kinds of civil engineering laboratory equipment. In providing services to visitors, CV Anugerah Sejati Prima has provided information about the specifications of the offered goods, but as an effort to obtain this information, visitors or potential buyers must come directly to the office or ask for information about the goods or services by telephone. The methodology used in making this system uses the agile method by applying the scrum framework. This application made by using PHP as the programming language by implementing the laravel framework. And by applying blackbox testing and accessibility testing as a system testing method. The result of this information system is that users or potential buyers can get price information and specifications by accessing the website, it can increase visibility and marketing of the CV. The presence of the website can also be used as evidence if CV Anugerah Sejati Prima exists and is trusted. By directing to the website, visitors or potential buyers will find complete information about the company, from the products being sold, the location, to the vision and mission, along with the company's history.